2022
DOI: 10.56407/2313-092x/2022-26(3)-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irrigation and weather conditions on the duration of interphase periods of winter wheat varieties

Abstract: The autumn growth and development of plants depend on a complex of external factors: the average daily air temperature, the amount of precipitation, the humidity of the seed layer of the soil, nutrients, light, etc. If winter wheat is sown at a later date, there are risks that the plants will enter the winter not well developed. It is possible to accelerate the passage of interphase periods with the help of irrigation, which is a necessary agrotechnical measure in the Southern Steppe of Ukraine. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that awned varieties have less resistance to lodging than awnless varieties (Korkhova et al, 2022). Current research partially confirms this.…”
Section: Source: Developed By the Authorssupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have shown that awned varieties have less resistance to lodging than awnless varieties (Korkhova et al, 2022). Current research partially confirms this.…”
Section: Source: Developed By the Authorssupporting
confidence: 77%
“…The research of M. Korkhova et al (2022) found that the determining criteria for selecting modern winter wheat varieties are the degree of durability and response to growing conditions. Each variety has certain morph-agrobiological traits and characteristics so that it can develop its genetic potential if a favourable environment is created for it.…”
Section: Introductionmentioning
confidence: 99%